Proteomic analysis of the copper resistance of Streptococcus pneumoniae1. Issue 3 (11th March 2015) - Guo, Zhong; Han, Junlong; Yang, Xiao-Yan; Cao, Kun; He, Ke; Du, Gaofei; Zeng, Guandi; Zhang, Liang; Yu, Guangchuang; Sun, Zhenghua; He, Qing-Yu; Sun, Xuesong
<x xml:space="preserve">Abstract</x> S. pneumoniae mainly increases cell wall biosynthesis and improves metabolic ability of many biological pathways to combat copper toxicity.